2008
DOI: 10.1111/j.1398-9995.2008.01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of work‐related airway allergies; summary of the advice from the Health Council of the Netherlands

Abstract: The Health Council of the Netherlands published a report in which the best procedure and method for recommending health-based occupational exposure limits (OELs) for inhaled allergens were identified by evaluating the scientific state of the art. Many respiratory disorders in the workplace arise from inhalation of substances which can cause allergy. To protect workers against respiratory allergy, various preventive measures are taken, one of them being reduction of exposure by setting legally binding standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Nonetheless, it has been suggested that 1 μg/g of Fel d 1 was associated with sensitisation, and 8 μg/g was related to asthma 30 37. Similarly, levels of Can f 1 to induce sensitisation and asthma symptoms were 2 and 10 μg/g, respectively 30.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it has been suggested that 1 μg/g of Fel d 1 was associated with sensitisation, and 8 μg/g was related to asthma 30 37. Similarly, levels of Can f 1 to induce sensitisation and asthma symptoms were 2 and 10 μg/g, respectively 30.…”
Section: Discussionmentioning
confidence: 99%
“…This discordance may be due to a low threshold for sensitisation [25] or tolerance and failure of specific IgE production due to repeated inhalatory antigen exposure [26,27] and also suggests the presence of a healthy worker effect [28]. Workers with soy-specific IgE may have avoided exposure to higher inhalable soy antigen concentrations through attrition or re-assignment to other areas.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Since exposure-response relations have been described especially for sensitizing agents, standard setting seems most promising for these agents. 22 Few exposure-response relations have been described for fungal constituents like glucans and extracellular polysaccharides (EPS) and this complicates a standard setting process.…”
Section: Risk Assessment and Exposure Limitsmentioning
confidence: 99%